“We’ve lost a lot of lives:” the impact of the closure of North America’s busiest supervised consumption site on people who use substances and the organizations that work with them - Morgan Magnuson; Shannon Vandenberg; Tracy Oosterbroek; Kevin Dey (Harm Reduction Journal)
Abstract Background Supervised Consumption Sites (SCS) are an evidence-based harm reduction intervention that reduces the risk of fatal drug poisonings. However, these approaches have faced political opposition in Canada, resulting in the closures of SCS in some provinces. Our study examines the aftermath of the closure of what was once North America’s busiest SCS, located in Lethbridge, Alberta, Canada, offering a contextualized exploration of regressive drug policies. Methods Our study adopts a descriptive qualitative design to explore the Lethbridge SCS closure and the city’s current state of harm reduction service provision. We conducted 37 interviews to understand the perspectives of people who use substances (PWUS) and staff members of organizations that provide harm-reduction services in Lethbridge. We chose to use reflexive thematic analysis, which allows for a critical realist and contextual approach to data analysis. Results We developed three themes based on our analysis. Our first theme speaks to the harms of SCS closures on PWUS and organizations that provide harm reduction services. Next, our second theme highlights participants’ perspectives on the political motivations behind the SCS closure. Our last theme explores how PWUS and organizations navigate the political opposition to harm reduction approaches while responding to the worsening unregulated drug poisoning crisis. Conclusions Our findings speak to the dangers of political decisions that restrict access to harm reduction services within the context of the current unregulated drug poisoning crisis.